1994
DOI: 10.1128/mcb.14.12.7867
|View full text |Cite
|
Sign up to set email alerts
|

Further analysis of cytoplasmic polyadenylation in Xenopus embryos and identification of embryonic cytoplasmic polyadenylation element-binding proteins.

Abstract: Early development in Xenopus laevis is programmed in part by maternally inherited mRNAs that are synthesized and stored in the growing oocyte. During oocyte maturation, several of these messages are translationally activated by poly(A) elongation, which in turn is regulated by two cis elements in the 3' untranslated region, the hexanucleotide AAUAAA and a cytoplasmic polyadenylation element (CPE) consisting of UUUUUAU or similar sequence. In the early embryo, a different set of maternal mRNAs is translationall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
56
0

Year Published

1995
1995
2003
2003

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 91 publications
(58 citation statements)
references
References 38 publications
2
56
0
Order By: Relevance
“…In previous experiments, we identified two Xenopus proteins with molecular sizes of 36 and 45 kDa that were UV crosslinked to the eCPEs of Cl1, Cl2, and ActR mRNAs (35,36). However, only the 36-kDa protein was cytoplasmic and therefore seemed the most likely one to be involved in mRNA polyadenylation in embryos.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In previous experiments, we identified two Xenopus proteins with molecular sizes of 36 and 45 kDa that were UV crosslinked to the eCPEs of Cl1, Cl2, and ActR mRNAs (35,36). However, only the 36-kDa protein was cytoplasmic and therefore seemed the most likely one to be involved in mRNA polyadenylation in embryos.…”
Section: Resultsmentioning
confidence: 99%
“…Members of this protein family do interact with the AUUUA degradation sequence (2,4,24). However, we should point out that the minimum number of uridine residues that can promote cytoplasmic polyadenylation in embryos is 12, which strongly correlates with the number of uridines required for binding of the 36-kDa protein/ElrA (34,35). Thus, if ElrA has a function related to mRNA degradation in early development, it would probably have to do so via this sequence, which has not previously been identified with this activity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It was first shown that Cl1/eRF1, Cl2 and activin receptor mRNAs were polyadenylated after fertilization due to a novel type of CPE-a poly(U) sequence (Simon and Richter, 1994;Simon et al, 1993Simon et al, , 1996. As mRNAs that contain this element are polyadenylated only after fertilization, this U-rich CPE is often called an embryonic CPE-in contrast to the UA-rich CPEs that are present within mRNAs that are polyadenylated during maturation.…”
Section: Cytoplasmic Polyadenylationmentioning
confidence: 99%